Pedicled frontal periosteal rescue flap via eyebrow incision for skull base reconstruction (SevEN-002) - Chang Ki Jang; Soo Jeong Park; Eui Hyun Kim; Jin Mo Cho; Ju Hyung Moon; Kyoung Su Sung; Je Beom Hong; Jaejoon Joon Lim; Minkyun Na; Chang-Ki Hong; Tae Hoon Roh; Jiwoong Oh (BMC Surgery, 2022)
Abstract Purpose Cerebrospinal fluid (CSF) leakage is one of the major complications after endoscopic endonasal surgery. The reconstructive nasoseptal flap is widely used to repair CSF leakage. However, it could not be utilized in all cases; thus, there was a need for an alternative. We developed a pericranial rescue flap that could cover both sellar and anterior skull base defects via the endonasal approach. A modified surgical technique that did not violate the frontal sinus and cause cosmetic problems was designed using the pericranial rescue flap. Methods We performed 12 cadaveric dissections to investigate the applicability of the lateral pericranial rescue flap. An incision was made, extending from the middle to the lateral part of the eyebrow. The pericranium layer was dissected away from the galea layer, from the supraorbital region towards the frontoparietal region. With endoscopic assistance, the periosteal flap was raised, the flap base was the pericranium layer at the eyebrow incision. After a burr-hole was made in the supraorbital bone, the pericranial flap was inserted via the intradural or extradural pathway. Results The mean size of the pericranial flap was 11.5 cm × 3.2 cm. It was large enough to cross the midline and cover the dural defects of the anterior skull base, including the sellar region. Conclusion We demonstrated a modified endoscopic technique to repair the anterior skull base defects. This minimally invasive pericranial flap may resolve neurosurgical complications, such as CSF leakage.